Does engaging in corporate social responsibility related activities enhance the stock performance of Asian firms? - Song, Wei-Hern. (2013)
As Corporate Social Responsibility (CSR) gains momentum in Asia, this paper examines how CSR affects Asian firms’ stock performance. A quantitative research using secondary data from Thomson Reuters ASSET4 and Worldscope shows that there is insufficient evidence to establish a bivariate relationship between CSR scores and the stock returns of firms. With the inclusion of the various control variables in the multivariate analysis, a weak negative correlation between CSR and stock performance was found. Moreover, the individual components of CSR that includes Environmental, Social, Governance and Economic have different impacts on stock returns. While the social and economic components of CSR have a weak negative influence on stock returns, the environmental component of CSR has a weak positive influence on stock returns in our regression model. The influence of the governance component of CSR on stock returns remains statistically insignificant. Our findings thus provide insights for investors to make investment decisions and also help managers to identify which aspects of CSR they should prioritise.